A study of derivational affixes forming noun in motivating book by brene brown - Yasa, I Wayan Wistika; Putra, IGB Wahyu Nugraha (Institut Pariwisata dan Bisnis Internasional, 2020)
This study expects to an investigation of morphological analysis of derivational affixes forming noun in Motivating Book by Brene Brown. The focuses of the study are to find the types of derivational affixes forming noun and to identify the function of derivational affixes by using the theory proposed by Katamba (1993) to analyze the types and theory proposed by Carstairs and McCarthy (2002) to describe the function of affixes. The data of the study was analyzed qualitatively and quantitatively, and observation method was used for collecting the data. The result found there are 4 types of prefixes forming noun, such as prefixes im-, in-, dis- and re-. Meanwhile, there are 13 types of suffixes forming noun, they are suffix -ing, -ness, -ion, -ity, -ment, -y, -ance, -ism, -er, -hood, -ship, -ian and -ist. Moreover, the functions of derivational affixes are class-changing affixes and class-maintaining affixes that found in this research.